2004
DOI: 10.1111/j.1442-9993.2004.01333.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of vegetation and vertebrate fauna to 23 years of fire exclusion in a tropical Eucalyptus open forest, Northern Territory, Australia

Abstract: This opportunistic study compares the vegetation, fuel loads and vertebrate fauna of part of a 120-ha block of tropical open forest protected from fire for 23 years, and an adjacent block burnt annually over this period. Total fuel loads did not differ significantly between the unburnt and annually burnt sites, but their composition was markedly different, with far less grassy fuel, but far more litter fuel, in the unburnt block. There were major differences between treatments in the composition of trees and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
72
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(81 citation statements)
references
References 50 publications
(93 reference statements)
6
72
1
Order By: Relevance
“…Modelled using quantile regression of non-eucalypt basal area and species richness against eucalypt basal area and species richness (s = 0.90, 0.75, 0.50, 0.25, 0.10). For basal area, the relationship was significant for all quantiles examined; for species richness, the relationship was not significant for any of the quantiles examined variation among plot-averaged metrics); (3) there is a considerable time-lag in basal area response of the eucalypt component to environmental drivers, particularly fire (compare Williams et al 1999;Russell-Smith et al 2003;Woinarski et al 2004), so that a lag in mortality of mainly large eucalypts may give the appearance of relatively invariant eucalypt basal area across the fire gradient. The strength of our analysis and conclusions derives from using many plots (n = 127) that are evenly scattered across the fire and rainfall gradient.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Modelled using quantile regression of non-eucalypt basal area and species richness against eucalypt basal area and species richness (s = 0.90, 0.75, 0.50, 0.25, 0.10). For basal area, the relationship was significant for all quantiles examined; for species richness, the relationship was not significant for any of the quantiles examined variation among plot-averaged metrics); (3) there is a considerable time-lag in basal area response of the eucalypt component to environmental drivers, particularly fire (compare Williams et al 1999;Russell-Smith et al 2003;Woinarski et al 2004), so that a lag in mortality of mainly large eucalypts may give the appearance of relatively invariant eucalypt basal area across the fire gradient. The strength of our analysis and conclusions derives from using many plots (n = 127) that are evenly scattered across the fire and rainfall gradient.…”
Section: Discussionmentioning
confidence: 88%
“…For example, at three tropical savanna sites in northern Australia with similar high rainfall (Solar village, Munmarlary and Kapalga) but different fire frequencies, varying from complete exclusion to frequent burns, there was a concomitant decline in the density of the non-eucalypt component, while eucalypt basal area was either not significantly different or increased in the burnt relative to unburnt plots (Williams et al 1999;Russell-Smith et al 2003;Woinarski et al 2004). The increase in eucalypt basal area at Munmarlary was attributed to an increase in the average size of stems rather than to significant additions AIC Akaike's Information Criterion; AIC c second order AIC for large and small sample sizes; w I the Akaike weight, representing the probability of a model being the 'best' in the candidate set; BA basal area a For each model, DAIC c is the difference between the model's AIC c value and the minimum AIC c of all models in the candidate set.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, many regional studies support the observation of recent monsoon rainforest expansion in a variety of regional, climatic and topographic contexts [5][6][7][30][31][32][33][34][35]. In various cases, the observed expansion of monsoon rainforests has occurred under relatively fire-prone conditions (e.g., [32,33,35]), indicating that enhanced growing conditions associated with increased regional rainfall especially from the 1950s [70,71], reduced evaporation from at least the 1970s [72], global CO 2 fertilisation [14,73], but see [74], and possibly grazing interactions through reducing fuel loads, are likely to have been contributory.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, many north Australian studies have reported expansion of typically small (<10 ha) patches or larger tracts of monsoon rainforest vegetation within the savanna matrix, particularly under higher rainfall conditions [5][6][7][30][31][32][33][34][35]. In different situations, such expansion has been attributed variously to reduced burning or browsing pressure, increased rainfall in recent decades, possible CO 2 fertilisation, and interactions between these.…”
Section: Introductionmentioning
confidence: 99%